SHORT TERM EFFECT OF LAPAROSCOPIC SLEEVE GASTRECTOMY ON CLINICAL, RENAL PARAMETERS AND URINARY NGAL LEVELS IN DIABETIC AND NON DIABETIC OBESITY - (:unkn) unknown (EDITURA ACAD ROMANE, 2019)
Background. Although diseases such as diabetes, hypertension, obstructive sleep apnea and hyperlipidemia are clearly documented as obesity associated diseases, it is not well-known whether obesity causes renal pathologies. The aim of the present study was to evaluate the effect of weight loss following laparoscopic sleeve gastrectomy on clinical, renal parameters and urinary Neutrophil gelatinase-associated lipocalin (NGAL) levels in diabetic and non-diabetic obese patients. Methods. Nineteen morbidly obese patients (10 diabetic and 9 non diabetic) who underwent laparoscopic sleeve gastrectomy were evaluated clinically (anthropometric measurements) and biochemically before surgery and at 6 months from surgery. Results. Significant decreases in weight, BMI, FPG, PPG and HbA1c levels were observed in the diabetic group when the baseline and 6th month parameters of the patients were compared. There was also a significant decrease in SBP and DBP. At 6th month following laparoscopic sleeve gastrectomy, renal parameters such as creatinine, mAlb/creatinine, NGAL/creatinine did not differ in the diabetic group. In the nondiabetic group, serum creatinine levels were significantly decreased, but other renal parameters such as mAlb/creatinine and NGAL/creatinine were not significantly different. Conclusions. Our findings revealed significant decreases in weight, body mass index and glycemic parameters after sleeve gastrectomy in diabetic and non-diabetic patients, while no significant alteration was noted in renal functions, urinary NGAL and microalbumin levels.
Keywords: sleeve gastrectomy; obesity; urinary NGAL; kidney; weight loss; T2DM; GELATINASE-ASSOCIATED LIPOCALIN; ALBUMIN EXCRETION; BIOMARKER; INJURY